Hypochlorite Oxidation of Benzaldehydes and Some of the p-Substituted Benzaldehydes: A Kinetic Study - Abdu Rahiman, K.K.; Radhakrishnan Nair, T.D. (Asian Journal of Chemistry, 2010)
Kinetic studies on the sodium hypochlorite oxidation of some aromatic aldehydes in aqueous acetic acid medium have been studied. The reaction showed first order dependence with respect to substrate and oxidant concentrations. The rate increased with increase in [H+] with fractional order dependence. Effects of ionic strength and dielectric constant of the medium have been investigated. Exner plots gave good correlation for different para-substituted benzaldehydes, which also gave good linear fits according to the Hammet equation.